ANALYSIS OF THE EFFECT OF LEADERSHIP, WORKLOAD AND JOB SATISFACTION ON ORGANIZATIONAL COMMITMENT OFFICES OF BAPPEDA AND LITBANG OFFICES, BULUNGAN REGENCY, NORTH KALIMATAN - Kaharuddin Kaharuddin; Ana Srie Kaningsih; Tri Darmayanti (STKIP Singkawang, 2022)
The purpose of this study was to examine and analyze influence leadership on employee job satisfaction, the effect of workload on employee job satisfaction, the influence leadership on employee organizational commitment, the effect of workload on employee organizational commitment and the effect of job satisfaction on organizational commitment of Bappeda and Litbang office employees, Bulungan Regency.The population in this study were all employees at the Department of Bappeda and R & D, Bulungan Regency, North Kalimantan, totaling 38 employees and the sample of this study was 38 employees. The analytical technique used in this research is path analysis with the help of SmartPLS software.The results showed that the leadership variable had a positive and significant effect on job satisfaction at the Department of Bappeda and Litbang, Bulungan Regency, North Kalimantan. The workload variable has a positive and significant effect on job satisfaction at the Bappeda and Litbang Office of Bulungan Regency, North Kalimantan. The leadership variable has a positive and significant effect on organizational commitment in the Bappeda and Litbang Office of Bulungan Regency, North Kalimantan. The workload variable has a positive and significant effect on organizational commitment in the Bappeda and Litbang Office of Bulungan Regency, North Kalimantan. The job satisfaction variable does not have a significant effect on organizational commitment at the Bappeda and Litbang Office of Bulungan Regency, North Kalimantan.